2009
DOI: 10.1002/aic.11989
|View full text |Cite
|
Sign up to set email alerts
|

Nitration of nitrobenzene at high‐concentrations of sulfuric acid: Mass transfer and kinetic aspects

Abstract: This article reports studies on mass transfer and kinetics of nitration of nitrobenzene at high concentrations of sulfuric acid in a batch reactor at different temperatures. The effects of concentration of sulfuric acid, speed of stirring, and temperature on mass transfer coefficient were investigated. The kinetics of nitration under homogenized conditions was studied at different sulfuric acid concentrations at these temperatures. The reaction rate constants were determined. The variation of rate constant wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…The value of k * increases with increasing temperature, and the value of n remains essentially unchanged. n is a specific thermodynamic parameter that is characteristic of different aromatic compounds, which is consistent with the conclusions reported in other studies 18,21,28 . The reaction rate parameters based on NO 2 + could decouple the H 2 SO 4 concentration from the reaction rate constant.…”
Section: Resultssupporting
confidence: 88%
See 3 more Smart Citations
“…The value of k * increases with increasing temperature, and the value of n remains essentially unchanged. n is a specific thermodynamic parameter that is characteristic of different aromatic compounds, which is consistent with the conclusions reported in other studies 18,21,28 . The reaction rate parameters based on NO 2 + could decouple the H 2 SO 4 concentration from the reaction rate constant.…”
Section: Resultssupporting
confidence: 88%
“…Numerous related studies 21,27,28 have shown that the rate of nitration is strongly related to the concentration of sulfuric acid. Within a certain range, the higher the concentration of sulfuric acid is, the faster the rate of aromatic nitration.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The conversion of NT first increased with the increasing of reaction temperature and then decreased, and the highest conversion was obtained at 340.2 K. The interaction between NT molecules and NO þ 2 ions increased with an increase in reaction temperature. The mass transfer rate of NT also increased and the reaction rate with the increase of temperature, as reported by Rahaman et al 28 However, NO þ 2 ions concentration decreased with an increase in temperature according to the reports by Edwards et al 29 The generation of NO þ 2 ions is through the catalysis of sulfuric acid, and the reaction is exothermic reaction. Therefore, the conversion would decrease as the reaction temperature reached a certain values in the nitration process of NT.…”
Section: Effect Of Reaction Temperature On the Conversionmentioning
confidence: 67%